2004
DOI: 10.1002/polb.20069
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of propylene–ethylene random copolymers

Abstract: Of the three melting peaks typical of a propylene-ethylene random copolymer (with 5.1 wt % ethylene) crystallized between 110 and 140°C, the two higher peaks result from primary and secondary isothermal crystallization, whereas the material crystallized on cooling gives the lowest peak. In contrast to polypropylene homopolymers, which show strong morphological changes developing from the center of a spherulite, copolymer specimens are uniformly crosshatched. The highest melting peak is related to an open cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…A different explanation must apply to the reduced thickening at the centres of a-polypropylene spherulites whose texture is quite open with two sets of nearly orthogonal lamellae [12]. Their fold surfaces do not touch but there is mutual contact on the growth surfaces, which will affect refolding and so delay thickening.…”
Section: Discussionmentioning
confidence: 98%
“…A different explanation must apply to the reduced thickening at the centres of a-polypropylene spherulites whose texture is quite open with two sets of nearly orthogonal lamellae [12]. Their fold surfaces do not touch but there is mutual contact on the growth surfaces, which will affect refolding and so delay thickening.…”
Section: Discussionmentioning
confidence: 98%
“…There is much debate surrounding the cause of the multiple melting endotherms,3,30–34 although there is usually a definite cause depending on the type of material that is being used and the conditions of analysis. Multiple melting endotherms could be the result of different polymorphic forms, melting‐recrystallisation, segregation by tacticity or molecular weight, the melting of different regions in the crystalline structure such as radial and transverse lamellae, or even orientation effects 3,30,31,33,35. Fraction A12 (115 °C), being the fraction with the most prevalent multiple melting, was analysed at different heating rates to determine if the cause of the multiple melting was due to a melting‐recrystallisation effect.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple melting endotherms could be the result of different polymorphic forms, meltingrecrystallisation, segregation by tacticity or molecular weight, the melting of different regions in the crystalline structure such as radial and transverse lamellae, or even orientation effects. [3,30,31,33,35] Fraction A12 (115 8C), being the fraction with the most prevalent multiple melting, was analysed at different heating rates to determine if the cause of the multiple melting was due to a meltingrecrystallisation effect. It should be noted at this point that all the samples exhibiting the multiple melting phenomenon have a single, narrow crystallisation peak.…”
Section: Crystallisation and Meltingmentioning
confidence: 99%
“…At high T c , the radial lamellae grow before the tangential lamellae, and thus the radial lamellae have greater thickness 43. Therefore, after crystallization at high temperatures, upon heating, the thin tangential lamellae melt first, and then the thicker radial lamellae melt 45–47. Weng et al demonstrated that different lamellar thicknesses cause multiple melting in metallocene‐catalyzed PP and in propylene‐ethylene random copolymers 46, 48…”
Section: Resultsmentioning
confidence: 99%